2021
DOI: 10.3389/fonc.2020.576855
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Micro-Ecological Changes and Potential Microbial Markers in Lung Cancer Patients

Abstract: The relationship between the microbiome and disease has been investigated for many years. As a highly malignant tumor, biomarkers for lung cancer are diverse. However, precision of these biomarkers has not yet been achieved. It has been confirmed that lung microecology changes in lung cancer patients compared with healthy individuals. Furthermore, the abundance of some bacterial species shows obvious changes, suggesting their potential use as a microbial marker for the detection of lung cancer. In addition, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 90 publications
(83 reference statements)
0
6
0
1
Order By: Relevance
“…Numerous investigations had indicated that the lung microbiota played multiple essential roles in lung diseases (27)(28)(29)(30)(31). However, previous studies had limitations in their characteristics to provide strong evidence, such as small sample size and lack of compliance with modern methodological research standards.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations had indicated that the lung microbiota played multiple essential roles in lung diseases (27)(28)(29)(30)(31). However, previous studies had limitations in their characteristics to provide strong evidence, such as small sample size and lack of compliance with modern methodological research standards.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Veillonella , Megasphaera , and Streptococcus presented a remarkably higher content in lung cancer patients than in healthy individuals. Similarly, Neisseria , Staphylococcus , and Dialister showed a higher level in lung cancerous lesions than in normal lung tissues ( Ran et al., 2020 ). However, different from the present study, one report found that Proteobacteria , Actinobacteria , and Firmicutes predominantly promoted the development of COPD by contributing the biosynthesis of palmitate, homocysteine, and urate ( Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different microorganisms cause different host immune responses. However, the microbiome not only acts on the organism by immunity responses, inflammation response, or metabolism mechanism, but also on the colonized organs locally ( Ran et al., 2020 ). For instance, fungal colonization and bacterial flora colonization were interacted with each other, which promoted the mycelial growth of fungi through colonized bacteria secreting antifungal substances and easily causing impaired lung infection ( Oever & Netea, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aumento relativo de Granulicatella spp, Abiotrofia spp y Streptococcus spp en pacientes con cáncer de pulmón. (Ran et al, 2021) Carcinoma de células escamosas de cabeza y cuello.…”
Section: Gen 16s Arnr En Esputounclassified